Patterns of larval fish assemblages along the direction of freshwater input within the southern branch of the Yangtze Estuary, China: implications for conservation. Issue 1 (1st January 2018) - Gao, Lei; Cheng, Fei; Song, Yiqing; Jiang, Wei; Feng, Guangpeng; Luo, Yuming; Xie, Songguang
ABSTRACT: The Yangtze Estuary is the largest estuary in the western Pacific Ocean, and harbors a high diversity of fish fauna. In this study, larval fish were surveyed monthly across three sections within the southern branch of the Yangtze Estuary (SBYE). A total of 49 taxa were collected, with 51.4% of the identified species being freshwater fishes. The collected numbers of larval taxa in the upper, middle, and lower sections were 22, 28, and 43, respectively. Species with differing salinity adaptations displayed different patterns along the direction of freshwater input. The collected numbers of larval taxa were 47 and 29 in the near-shore and mid-stream areas, respectively; and the abundances of larval fish in the near-shore areas tended to be higher than in the mid-stream areas in all the three sections. Larval fish occurred year-round with two peaks of abundance. Our results suggest that the freshwater input was the dominant factor shaping larval fish assemblage structure and dynamics within the SBYE. Influences of the Three Gorges Dam and South-to-North Water Transfer Project on larval fish assemblages within the SBYE should be considered with regard to conservation practices.